A Semantic Framework for E-Commerce Using Web Ontology Language 2 - Jimoh, R.G.; Kinssinger, S.; Agbo, F.J.; AbdulRaheem, M.; Tomori, R.A.; Salimonu, I.R. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Several web applications have been deployed by business enterprises through which their products would not only be made available on the internet, but also enable their prospective consumers to be able to follow some procedures to make their purchases online. This is normally achieved with the help of some technologies provided by the Semantic Web, namely Resource Description Framework (RDF), Resource Description Framework Schema (RDFS), DARPA Agent Markup Language (DAML) plus Ontology Inference Layer (OIL) and Web Ontology Language (OWL1). The Present study leverages on some of the Semantic Web technologies mentioned in the previous sentence in order to design a Semantic framework for enhancing Business to Consumer (B2C) e-commerce applications. In this paper, the researchers developed OWL 2 ontology rich in more expressive OWL constructs for rich entailments. Qualified Cardinality Restriction (QCR) which OWL 2 is known for, is also applied to the ontology. Also in this paper, the researchers compared two popular reasoners in querying the underlying ontology in a programmatic way. The overall aim of this research is to provide a more efficient framework for B2C through the right choice and combination of some Semantic Web languages.